Effect of Growth Regulators on in-vitro Callusing of Wild Variety of Withania somnifera L. in B5 Medium - Gaurav, Naveen; Kumar, Arun (Indian Forester, 2020)
"Ashwagandha" products are one of the major herbal components of various disease tonics mentioned in Indian systems of medicine. It is an erect branching under shrub reaching about 150 cm in height, usually clothed with minutely stellate tomentum; leaves ovate up to 10 cm long, densely hairy beneath and sparsely above, flowers are greenish or yellow in axillary fascicles, bisexual, pedicel long, fruits globose berries which are orange coloured when mature, enclosed in a persistent calyx. The fleshy starchy roots of Ashwagandha when dry, they are gradually tapering down with a brownish white surface, cylindrical and pure white inside when broken. Majority of the constituents are with anolides (steroidal lactones with ergostane skeleton), glyco with anolides and alkaloids. These include with aferin A, withanolides G & D, sitoindosides and with asomnine. It helps to induce the body by rejuvenating the reproductive organs, just as a tree is invigorated by feeding the roots.